Pengaruh Temprature Humidity Index (THI) dan Persepsi Wisatawan Terhadap Minat Berkunjung Di Kawasan Ekowisata Bale Mangrove, Desa Jerowaru Kabupaten Lombok Timur : Influence of Temperature Humidity Index (THI) and Visitor Perception on Visiting Interest in The Mangrove Bale Ekowisata Area ff Jerowaru Village East Lombok District - Putri, Zahwa Sahendah; Webliana, Kornelia; Wulandari, Feriana Tri (HUTAN TROPIKA, 2024)
Bale Mangrove is one of the tourist attractions on East Lombok's coast that emphasizes ecotourism. The number of tourist visits at this location has increased significantly in 2023. This study was conducted to measure the level of tourist comfort at Bale Mangrove Ecotourism, based on temperature and humidity or Temperature Humidity Index (THI), and identify factors that can influence tourist interest in revisiting this area. Studies related to tourist comfort on tour are critical because they can affect tourist satisfaction with the tourist destinations visited and their intention to visit again. The method used in this research is descriptive quantitative, with the location selection based on the consideration that Bale Mangrove ecotourism is a relatively new destination, increasingly popular, and the number of visitors is increasing. Measurements were made in two ways, namely (1) direct measurement of air temperature and humidity conditions at mangrove locations with different density types (Meeting, Medium, Rare), and the results obtained then calculated the THI value; (2) based on the results of tourist perceptions related to existing conditions in Bale Mangrove Ecotourism. Analysis was carried out using a Likert scale to identify factors using linear regression. The results showed that the average daily temperature ranged from 27.4 ° C to 28.9 ° C, daily humidity ranged from 62% to 82%, and THI values of 25.9 to 27.4, which can be categorized as less comfortable. Based on the research results, the thermal comfort aspect shows a comfortable category with a percentage of 75%, accessibility parameters with a percentage of 75%, amenity with a percentage of 61%, and interest in visiting with a percentage of 74%. Regression analysis shows that temperature, humidity index, and perceived comfort simultaneously affect visiting interest.